2022
DOI: 10.3390/jrfm15110518
|View full text |Cite
|
Sign up to set email alerts
|

GHG Emissions and Economic Growth in the European Union, Norway, and Iceland: A Validated Time-Series Approach Based on a Small Number of Observations

Abstract: This research aims to ensure methodological conformance and to test the validity of its empirical application. To do so, the study analysed differentiation of the development patterns of four time-series variables. The relationships between greenhouse gas (GHG) emissions, employment, inflation, and gross domestic product (GDP) at constant prices were analysed, comparing the European Union (EU-27) and two European Free Trade Association countries. The study period covers twelve years of monthly and quarterly da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The investigation of the H2 hypothesis explores the possibility of clustering EU member countries into homogeneous groups based on key features, like forest area, economic performance, green performance, and greenhouse gas emissions (GHG). The cluster analysis results confirm this hypothesis by identifying distinct groups of countries with similar characteristics in these domains, consistent with the findings of other researchers [3,5,42,49]. Cluster A comprises countries with high forest coverage (60.50%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The investigation of the H2 hypothesis explores the possibility of clustering EU member countries into homogeneous groups based on key features, like forest area, economic performance, green performance, and greenhouse gas emissions (GHG). The cluster analysis results confirm this hypothesis by identifying distinct groups of countries with similar characteristics in these domains, consistent with the findings of other researchers [3,5,42,49]. Cluster A comprises countries with high forest coverage (60.50%).…”
Section: Discussionsupporting
confidence: 91%
“…Forests are crucial in carbon sequestration, maintaining balance in the global carbon cycle [49,51]. Adequate afforestation and reforestation efforts can counterbalance the loss of natural forests and contribute to increased biodiversity and the protection of species' natural habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by [46] examined the impact of various macroeconomic variables on the economic growth of the 27 member states. The study's preliminary results show that G.D.P.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that carbon intensity target shocks had a negative impact on the tourism aggregate economy, while the reduction in carbon intensity target offset the positive effects of productivity shocks and increased the negative carbon impacts. Furthermore, different carbon intensity targets produce various volatilities and the persistence of exogenous shocks (e.g., Gricar et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%